2019
DOI: 10.7759/cureus.6100
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Facial Nerve Branches and Anatomical Landmarks for Its Trunk Identification: A Pilot Cadaveric Study in the Lithuanian Population

Abstract: ObjectiveThe purpose of this study was to evaluate facial nerve (FN) branching variations based on Davis and Kopuz classifications in the Lithuanian population and measure the shortest distance from the facial nerve trunk (FNT) to its anatomical landmarks.MethodsTwenty-two hemifaces of 11 cadavers were dissected. The preauricular skin cut was made and extended behind the ear lobe and along the inferior border of the mandible. The skin with subcutaneous tissue and superficial fascia were separated and medially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The literature reports several variants of the main trunk of the facial nerve by which the nerve may be split into 2 or even 3 trunks within the mastoid segment exiting through separate osseous foramina, or even more different variants on the same person from one side of the face compared to the other. 5 We suspect that our patient has a superficial variation of the facial nerve.…”
Section: Discussionmentioning
confidence: 87%
“…The literature reports several variants of the main trunk of the facial nerve by which the nerve may be split into 2 or even 3 trunks within the mastoid segment exiting through separate osseous foramina, or even more different variants on the same person from one side of the face compared to the other. 5 We suspect that our patient has a superficial variation of the facial nerve.…”
Section: Discussionmentioning
confidence: 87%
“…Anatomy of FN was investigated previously in many studies [ 8 , [13] , [14] , [15] ] and different landmarks were studied by surgical and anatomical studies, for assistance of surgeons to safely recognize the FN, for instance, some authors stated that posterior belly of digastric muscle (DGM) is good reference landmark for recognition of FNT [ 16 ], while other investigators reported that styloid base and the posterior belly of DGM origin considered better and safe bone landmarks for the identification of FNT [ 17 ], as a consistent superficial bony landmarks, the mandible angle and the tip of mastoid process were considered by other studies to identify the trunk [ 18 ]. However, there is still much debate about the most reliable and safest landmarks.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still much debate about the most reliable and safest landmarks. Authors, proposed that the best landmark should be easily palpated and superficial in location which not need complete deep tissue resections [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations